ECONOMIC AND SOCIAL DEVELOPMENT - Muhitdinova Nargiza Anvarovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The article examines the development of economic competencies of the students. In the conditions of reforming the economy of Ukraine, the modern paradigm of education involves the training of a highly skilled future economists. The purpose of the article is to show the importance of formation of the students’competencies. On the basis of generalization of literary sources we can determine the structure of professional competence of future specialists of the economic sphere. It has been proved that the purpose of the development of personal competences is to stimulate students' interest in economic disciplines, form the ability to freely use professional economic terminology, promote the abilities of gifted students, involve students in active participation in various conferences, professional contests, etc. Also the article shows the necessity of creation of the pedagogical conditions in which the competences should be formed.